Terapia integrativa sistémico-ocupacional en un caso de trastorno neurocognitivo mayor no especificado. - Condoy Yaguachi, Juan Miguel (My University, 2021)
The aim of this work is to develop a therapeutic plan for a case with unspecified major neurocognitive disorder, it consists of ten sessions carried out under the integrative approach with systemic and occupational therapy. In this research, a search for definitions, ethology and prevalence of the disorder was carried out, symptomatology at cognitive level with physical affectation was evidenced, in addition, the course and development of the major neurocognitive disorder. As for the treatment, techniques that favor the well-being and autonomy of the patient are incorporated; on the other hand, it is important to mention that the methodology used in the research is descriptive, through a review of updated bibliography relevant to the research topic. The lifestyle of patients with unspecified major neurocognitive disorder is affected in various areas, such as family, social and work, therefore, it is necessary to incorporate a comprehensive work with family, to strengthen the emotional state, regain autonomy and stop cognitive impairment in patients.
El presente trabajo tiene como objetivo desarrollar un plan terapéutico para un caso con trastorno neurocognitivo mayor no especificado, consta de diez sesiones realizadas bajo el enfoque integrativo con terapia sistémica y ocupacional. En esta investigación se realizó la búsqueda de definiciones, etología y prevalencia del trastorno, se evidencio sintomatología a nivel cognitivo con afectación física, además, del curso y desarrollo del trastorno neurocognitivo mayor. En cuanto al tratamiento se incorporan técnicas que favorecen el bienestar y autonomía del paciente, por otra parte, es importante mencionar que la metodología que aborda la investigación es de tipo descriptiva, a través de revisión bibliografía actualizada y de relevancia al tema de investigación. El estilo de vida que tienen los pacientes con trastorno neurocognitivo mayor no especificado se ve afectado en los diversos ámbitos, como los familiares, sociales y laborales; por consiguiente, es necesario incorporar un trabajo integral con familia, para fortalecer el estado emocional, recuperar autonomía y detener el deterioro cognitivo en paciente
Keywords: TRASTORNO NEUROCOGNITIVO; ALTERACION COGNITIVA; INTERVENCION TERAPEUTICA